A era dos direitos em Norberto Bobbio: fases e gerações - Oliveira, Samuel Antonio Merbach de (2010)
The thesis has as objective to answer equally to the philosophical union between the phases and the generations of rights of the man. ln turn, the specific objectives are: to study the historical evolution of the rights of the mau since the antiquity until the contemporaries treats; to show that the choice of the person as a new citizen of international law can guarantee the protection of the dignity of the human being; to examine the development and to effect of the rights of the man in the contemporary society in agreement of the teachings of Norberto Bobbio. The Age of the Rights subject in Norberto Bobbio: Phases and Generations are of great relevance, therefore, following the trend of the contemporary philosophy, the recognition and the protection of the rights of the man are presented in the Constitutions of the modern democratic States, as we has in the international system of rights of the man, representing a way to long for the ideal of the pacific coexistence between the nations. For Bobbio the most important problems of our time are mentioned to the rights of the man and to the peace, in the way that the solution for the peace problem depends on our survival; and the solution of the rights of the man problem is the only certain signal of the civil progress. Bobbio understands this reason, the dialogue and the moderation are specific and valid elements of the culture and the human being condition to minimize the disrespect and the breaking of the rights of the man in the contemporary society, even in a historical time of great violence and not of lesser injustices. To the Bobbio's philosophy the Rights afield Man are developed in four phases: the first phase -Right Born Universal moment where the Natural Rights was not positive; the second phase -Particular Positive Rights are characterized for the fact of the State recognizes part of the Natural Rights in Constitution Letters (particular positive); the third phase -Universal Positive Rights examines the magnifing of the recognition of the Natural Rights and its positive consequent that occurs by means of Treat International(universal positive)and the fourth phaseis called phase of Specification deals with the gradual passage for a later determination of the titular citizens ot rights. In a complementary way, the jointed previously phases have five deriving generations of the historical development of the rights of the man: Ia Generation -the Individual Rights: that estimates individual freedoms and the formal equality in front of the law; 2a Generation -the Colective Rights: established on the social rights that have for objective to guarantee to the people material conditions as essential for the full joy of their rights, where detaches the right to 'the work; 3a Generation - the Rights of Fraternity or Solidarity: deals with the collective and diffuse rights, that basically understand the environrnental and the consumer rights; 4a Generation: The Rights of Genetic Manipulation: that are related with the biotechnology and to bioengineering, reflecting ethical concerning questions of life and death. Although the Bobbio's philosophy has not placed the peace as element of fifth generation, Bobbio gave a special attention to the subject of the peace. In fact, if Bobbio was present in the current days, certainly would have replaced the peace of third for the fifth Generation of the Rights of the Man, for considering it as necessary estimated for the recognition and the effective protection rights of the man in each State. Finally, the conclusion deals with the roain arguments pointed out in the course of the thesis in front of the referring observations to the rights of the man. In this association, was overcome a position concerning the diverse problems and the viable solutions to subject them, printing evaluations of the points longed for in the thesis